Experimental Study of Mechanical Characteristics of Tunnel Support System in Hard Cataclastic Rock with High Geostress - Minglei Sun; Yongquan Zhu; Xinzhi Li; Zhengguo Zhu; Benguo He (Shock and Vibration)
In hard cataclastic surrounding rock with high geostress, the rock monomer strength is high and the rock is broken, and tunnel excavation in it is apt to cause large deformation, collapsing, and breaking, causing initial support crack and even intruding of the initial support deformation. The characteristics of the support system under different support parameters and shapes are analyzed, and the reasonable support section shape and support parameters are determined. The results showed that (1) under the condition of high geostress and hard cataclastic surrounding rock, the initial support deformation is large, the horizontal convergence is much larger than the settlement of arch, and the deformation duration is relatively short; (2) the distribution of pressure and stress in initial support are very uneven on the cross-section and greatly affected by the construction process; (3) in the case of large horizontal tectonic stress, the use of large curvature side wall support is beneficial to improve the quality of support and control the deformation of the structure, especially to improve the stress of concrete; (4) the closure time of the supporting system greatly influences the stress state and deformation, so it is necessary to shorten the length of the lower bench and the distance of the invert as possible so as to close the support as early as possible; (5) different location of the tunnel surrounding rock stress distribution is very uneven, the measured value is much larger than calculated value in level III based on the specification of surrounding rock; (6) under high strength and ground stress, the initial supporting stress of steel frame increases rapidly, and the measured stress is larger. This indicates that the steel frame structure bears heavy early load. Therefore, the stiffness of the steel frame should be as large as possible to meet the loading requirements.